2016
DOI: 10.1590/0103-6440201601107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sonic Vibrations on Bond Strength of Fiberglass Posts Bonded to Root Dentin

Abstract: Sonic vibrations may improve the bond strength and durability of fiberglass posts by improving adhesive penetration into dentin as well as the cement flow. The objective of this study was to evaluate the effect of sonic vibrations on the bond strength between fiberglass posts and root dentin using the pull-out test. Bovine roots were endodontically treated and divided randomly into four groups (n=12): Group C - conventional cementation (control); Group SA - sonic vibration (Smart Sonic Device, FGM) of the adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 20 publications
1
10
0
4
Order By: Relevance
“…Some studies have demonstrated that the sonic application of adhesive materials may be an excellent alternative for improving the interaction of these materials with the mineral structure of dentin [11,13,14,23,24]. The present study demonstrated that the use of the ultrasonic technique improved the performance of the self-adhesive resin cements RelyX U200 and Bifix SE.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Some studies have demonstrated that the sonic application of adhesive materials may be an excellent alternative for improving the interaction of these materials with the mineral structure of dentin [11,13,14,23,24]. The present study demonstrated that the use of the ultrasonic technique improved the performance of the self-adhesive resin cements RelyX U200 and Bifix SE.…”
Section: Discussionsupporting
confidence: 58%
“…An oscillating wave across the cement increases the fluidity, leading to a reduction in viscosity and consequently providing a greater power of diffusion [25]. Recently, one study showed that sonic devices resulted in films with fewer defects and that the use of sonic vibrations during the post accommodation process enhanced the cement flow [23]. Most authors investigating the effect of sonically applied dental material used ultrasonic devices.…”
Section: Discussionmentioning
confidence: 99%
“…The use of sonic vibration has also been proposed to improve the bond of the resin cement to fiberglass posts, favoring the flow of the cement and post accommodation. 6 Studies have suggested that sonic application of etch-and-rinse adhesives can increase the bond strength to coronal dentin because sonic devices sónica durante la acomodación posterior y las condiciones de envejecimiento (24 horas agua destilada o 5.000 ciclos térmicos). Los postes de fibra de vidrio (White Post DC1, FGM) se limpiaron con alcohol, se trataron con silano y se cementaron con cemento de curado dual (Allcem Core, FGM) o con cemento de resina autoadhesivo (seT, SDI).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies reported the effect of sonic application directly on the post to improve the bond strength when compared with manual accommodation. 6,13 It has been reported that a sonic device for accommodating posts during the luting procedure resulted in more homogeneous films, with less defects and bubbles. 6 The Smart Sonic Device is a vibrating sonic energygenerating device that would be able to improve the diffusion and accommodation of different dental materials used in direct and indirect restorations.…”
Section: Introductionmentioning
confidence: 99%
“…A pesar de que estos tres cementos son duales se requieren de una luz de fotocurado para completar su polimerización. El cemento adhesivo será fotocurado a una profundidad de 2mm con una lámpara LED y polimerizado de forma química en una profundidad mayor a 2 mm (28)(29)(30) .…”
Section: Desafío Erosivounclassified